2019
DOI: 10.1097/ta.0000000000002165
|View full text |Cite
|
Sign up to set email alerts
|

Redefining postinjury fibrinolysis phenotypes using two viscoelastic assays

Abstract: INTRODUCTION: Fibrinolysis was initially defined using rapid thrombelastography (rTEG). The cutoffs for the pathologic extremes of the fibrinolytic system, hyperfibrinolysis and shutdown, were both defined based on association with mortality. We propose to redefine these phenotypes for both TEG and for rotational thrombelastometry, the other commonly used viscoelastic assay. METHODS: Rotational thrombelastometry, rTEG, and clinical data were prospectively collected on trauma patients admitted to an urban Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 33 publications
1
75
0
2
Order By: Relevance
“…However, it is still under debate whether prophylactic or therapeutic administration of TXA should be performed in hospitals with access to viscoelastic testing [145][146][147][148][149][150][151][152][153][154][155]. Physiologic fibrinolysis and fibrinolysis shutdown are defined in ROTEM as an EXTEM LI60 82-97.9% and ≥ 98%, respectively [156].…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…However, it is still under debate whether prophylactic or therapeutic administration of TXA should be performed in hospitals with access to viscoelastic testing [145][146][147][148][149][150][151][152][153][154][155]. Physiologic fibrinolysis and fibrinolysis shutdown are defined in ROTEM as an EXTEM LI60 82-97.9% and ≥ 98%, respectively [156].…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…72 In another bi-institutional cohort study including 2,540 severe trauma patients, Moore's group reported fibrinolysis shutdown in 46% of patients followed by a physiological state (36%) and hyperfibrinolysis (18%). 37,77 They further showed an independent association between fibrinolysis shutdown and mortality compared with physiological fibrinolysis. Their diagnostic criteria for the spectrum of fibrinolysis states was based on TEG LY30: shutdown 0.8%, physiological fibrinolysis of 0.9 to 2.9%, hyperfibrinolysis 3% at admission.…”
Section: Postinjury Fibrinolysis: Not An Open or Shut Casementioning
confidence: 93%
“…3,32 What has emerged in recent years is that it is no longer sufficient to rely solely on plasmatic prothrombin time, international normalized ratio, or activated partial thromboplastin time to diagnose coagulopathy and guide treatment. 3,[33][34][35][36][37] Other trauma trials suggest that similar limitations may also apply to relying exclusively on single point parameters from viscoelastic methods (e.g., clot times and indices of clot lysis). [38][39][40] Fig .…”
Section: Trauma-induced Coagulopathy: a Bewildering Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations